THE STUDY OF MAST CELLS IN VARIOUS THYROID DISORDERS - RAJESH.S.PATIL; RASHMI.K.PATIL; V.L.PATTANKAR; SAINATH.K.ANDOLA; SOWMYA.R.PATIL; SREEKANTHA (International Journal of Pharma and Bio Sciences, 2013)
Mast cells are distributed throughout the body, increased proportions are present in the skin, respiratory tract, gastrointestinal tract, uterus and urinary bladder but functions of mast cell in health and disease are not well understood. Mast cell granules store wide variety of mediators of inflammation like heparin, histamine, serotonin, 5-HT, various chemotactic factors, slow reacting substances of anaphylaxis, prostaglandins and various enzymes and their release signals a number of physiological defense responses. The mast cells play a vital role in various inflamatory and immunopathologic reactions often linking the humoral and cell mediated phases of the process. Mast cell alterations have been documented in neoplasms, alteration number of mast cells discharging their granules is observed in goitre and adenomatous thyroid;hence the present study documents the study of relation of mast cells in various thyroid disorders.